3D traffic noise mapping using unstructured surface mesh representation of buildings and roads. (1st December 2017) - Zhao, Wei-Jiang; Liu, En-Xiao; Poh, Hee Joo; Wang, Binfang; Gao, Si-Ping; Png, Ching Eng; Li, Kelvin Wenhui; Chong, Shyh Hao
Abstract: A method is presented for three-dimensional (3D) road traffic noise mapping with unstructured surface meshes of buildings and roads. Owing to the ability of the surface mesh to represent objects with high complexity geometry, the method enables 3D noise mapping with realistic building and road models. A road quadrilateral mesh model is built with the coordinates of its vertices captured from the original road triangular mesh. Instead of using the traffic data, we apply the road emission noise levels established by field measurements for a prior classification of roads to determine the basic noise level. An angle scanning based algorithm is developed for modelling 3D noise propagation in urban environments, with obstructions between virtual receiver points and road segment sources are efficiently considered. Verification and validation examples involving high-rise buildings are presented, as well as several 3D noise mapping examples.